PEMANFAATAN TEKNOLOGI DIGITAL DALAM PEMBELAJARAN KETERAMPILAN MENYIMAK: ANALISIS LITERATUR - Musawir, Muhammad; Hasbi, Nur; Nurrahma, Nurrahma (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2024)
This study aims to analyze the patterns, effectiveness, and impact of digital technology use in listening skills instruction based on recent literature. The method employed is a literature review, analyzing 30 reputable journal articles published between 2019 and 2024. The findings reveal that audio-visual media (50%) and gamification-based learning applications (35%) are the most utilized technologies, resulting in an average improvement in listening skills scores by 21.5% and enhancing students' learning independence. Podcasts also significantly contribute to critical listening skills despite being employed in only 15% of learning patterns. The study concludes that digital technology effectively enhances listening skills and empowers students to learn independently. Recommendations include providing digital literacy training for teachers, integrating technology into curricula, and conducting further research on the specific effectiveness of digital platforms such as podcasts and gamification in language learning contexts.